Inpatient versus Outpatient Total Knee Arthroplasty - Edwards, Paul K.; Milles, Jeffrey L.; Stambough, Jeffrey B.; Barnes, C. Lowry; Mears, Simon C. (The Journal of Knee Surgery, 2019)
The rise of improved perioperative recovery protocols after total knee arthroplasty (TKA) has led to faster, more streamlined hospital stays for many patients. Combined with the implementation of value-based care and bundled payment initiatives, there has been a paradigm shift toward outpatient TKA surgery. This change to practice has been accelerated by recent policy changes enacted by the Center for Medicaid and Medicare Services regarding the removal of TKA as an inpatient only procedure as well as some insurance companies denying preauthorization for inpatient stays after TKA. Our review aims to address the inclusion and exclusion criteria for outpatient TKA consideration, examine the outcomes for outpatient joint replacement surgery, and discuss limitations of widespread adoption for same-day discharges.
Keywords: arthroplasty; outpatient; inpatient; total knee arthroplasty